The influence of contextual factors on an intervention for people with disabilities from support persons' and health personnel's perspectives: a focus group study - Anette Granberg; Lars-Olov Lundqvist; Anna Duberg; Marie Matérne; Marie Matérne (Frontiers Media S.A., 2024)
IntroductionContextual factors influence interventions in healthcare and pose a particular challenge in interventions designed for people with profound intellectual and multiple disabilities (PIMD). Exploring support persons' and health personnel's experience of an intervention may improve our understanding of the influence of contextual factors. Such exploration is important for revealing areas and focus points for future implementations. Therefore, the aim of this study is to explore support persons' and health personnel's experience of contextual factors during involvement in an intervention for people with PIMD.MethodsThis focus group study includes eight groups, comprising a total of 34 support persons and health personnel, at habilitation centres at four regions in central Sweden. Data were analysed inductively using a content analysis approach.ResultsThree themes emerged from the analysis of the informants' perspectives on the contextual factors: (1) structure and support enhances intervention feasibility; (2) an intervention's benefit for people with PIMD increases its acceptability; and (3) being engaged and involved increases support persons' and health personnel's motivation. Our findings show that the implementation of an intervention for people with PIMD should focus on the recipients of the intervention in its context, forming a clear communication plan. A training programme should be provided for the recipients and providers of the intervention.DiscussionFinally, the implementation process can be facilitated by creating space for staff to contribute and by encouraging participation and ownership for everyone involved. Using a co-design strategy can enable a shared responsibility to solve the identified challenges, while contributing to the development and design of future interventions for people with disabilities.